Fenomena pacaran di kampus Universitas Islam Negeri Maulana Malik Ibrahim Malang - Fadhilla, Nur (Maliki Interdisciplinary Journal, 2026)
Dating is a form of social relationship frequently found among adolescents and university students, including in Islamic higher education institutions such as the State Islamic University (UIN) Maulana Malik Ibrahim Malang. This phenomenon is influenced by various internal factors, such as the psychological development of late adolescents, emotional needs, and a lack of appreciation of religious values, as well as external factors such as the influence of globalization, popular culture, and the modern social environment. This study aims to examine the phenomenon of dating among UIN Malang students, including the causal factors and the impacts on students’ academic, psychological, and spiritual lives. This study uses a qualitative method with a descriptive approach to understand the phenomenon in depth based on the campus’s social and religious context. The results of the study indicate that dating can have various negative impacts, including impaired concentration in learning, decreased productivity, emotional and psychological stress, the risk of violence in relationships, and the potential for promiscuous sexual behavior that is contrary to Islamic values. However, dating can also have positive impacts if undertaken wisely, healthily, and responsibly, such as serving as a source of motivation and emotional support. Therefore, it is necessary to strengthen character building, religious understanding, and self-control so that students are able to balance emotional needs with Islamic values ​​that are characteristic of UIN Malang.